1998
DOI: 10.1093/humrep/13.suppl_4.184
|View full text |Cite
|
Sign up to set email alerts
|

Human assisted conception: a cautionary tale. Lessons from domestic animals

Abstract: A variety of embryo-based technologies used in farm animal reproduction, including embryo culture, nuclear transfer, embryo-somatic cell co-culture and asynchronous embryo transfer can lead to the production of large offspring; the so-called large calf/lamb syndrome. In some cases, abnormalities in the fetus and newborn are apparent. The nature of these associations is explored with emphasis on the biological differences between in-vivo- and in-vitro-produced embryos. A unifying framework and research programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 70 publications
4
71
0
Order By: Relevance
“…23 Scrutinizing the endometrial environment in the first week of pregnancy, when implantation occurs, the main difference between IVF and spontaneous pregnancies is the hormonal support routinely given to women in the IVF group. During the study period women treated in our IVF unit received estrogenic and progestative support in the first 10-12 weeks of pregnancy [usually Estrofem (estradiol; Novo Nordisk, Begsraerd, Denmark), 2 mg three times daily orally, and Utrogestan (micronised progesterone; Ferring Pharmaceuticals Ltd, Saint-Prex, Switzerland) 400 mg twice daily intravaginally].…”
Section: Discussionmentioning
confidence: 99%
“…23 Scrutinizing the endometrial environment in the first week of pregnancy, when implantation occurs, the main difference between IVF and spontaneous pregnancies is the hormonal support routinely given to women in the IVF group. During the study period women treated in our IVF unit received estrogenic and progestative support in the first 10-12 weeks of pregnancy [usually Estrofem (estradiol; Novo Nordisk, Begsraerd, Denmark), 2 mg three times daily orally, and Utrogestan (micronised progesterone; Ferring Pharmaceuticals Ltd, Saint-Prex, Switzerland) 400 mg twice daily intravaginally].…”
Section: Discussionmentioning
confidence: 99%
“…Techniques that can lead to a predisposition to fetal oversize include embryo culture [14,15], embryo-somatic cell co-culture [3] and asynchronous embryo transfer [16], but the causal factors have not been identified. It is thought that the nature of these abnormalities is associated with the biological differences between in vivo-and in vitro-produced embryos [18]. Farin and Farin [3] have reported that at 7 months of gestation, fetuses from IVP embryos produced by co-culture with oviductal epithelial cells in TCM 199 supplemented with 10% estrous cow serum were heavier than fetuses from IVD embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, glucose and pyruvate uptake and utilisation as well as oxygen uptake were comparable between in vivo-and in vitroderived embryos, but differed at the cellular level, with increased cellular metabolism for in vitro embryos [34]. Increased oxidative metabolism could in turn induce higher production of reactive oxygen species leading to oxidative stress [21]. ] .…”
mentioning
confidence: 99%